(untitled) (Research, Society and Development, 2022)
Non-obstetric surgical interventions in pregnant women, despite having a low incidence, occur, and require further studies regarding the anesthesiological management, due to pregnancy being a period marked by physiological, hormonal and anatomical changes for the mothers, and of great cell differentiation and growth. for embryos and/or fetuses, which their exposure to drugs can be a risk factor for development. The aim of this study is to analyze the implications of anesthetic management in non-obstetric surgeries during pregnancy. This work is a systematic review of the literature, carried out through articles published in English, between 2017 and 2022, published in the PUBMED and VHL databases, with the following descriptors: pregnancy, anesthesia, congenital abnormalities. It was found that: neuraxial anesthesia is more indicated in the first trimester, due to lower toxicity; low fetal weight associated with general anesthesia; most surgeries are abdominal and occurred in the second trimester under general anesthesia; higher prevalence of premature births in pregnant women who underwent surgery in the third trimester; need for surgical planning, anesthetic management and fetal monitoring according to the physiological particularities of each pregnant woman; and brain neurotoxicity proven in animal tests. Anesthesiological planning is essential to minimize the risks of fetal exposure to toxicity and teratogens, however, it is valid to show that anesthetics, provided they are applied in standard dosages, do not present serious risks to the development of the fetus, but in addition to multidisciplinary care, it is essential that new studies are carried out to assess the brain neurotoxicity of these drugs in fetuses.